KERAGAAN PERTUMBUHAN AWAL ENAM KLON TEBU (Saccharum officinarum L.) ASAL SEDIAAN BIBIT BAGAL, MATA RUAS TUNGGAL, DAN MATA TUNAS TUNGGAL - , DEVITA AREIFVIA NINGSIH, Dr. Ir. Taryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sugar is one of community and industry daily demands. To improve national sugar economics, high productivity that is dependent on sugarcane final yield and sucrose content is required. Sugarcane final yield and sucrose content are influenced by planting material. Due to the important of planting material, this study is intended to examine the influence of planting materials i.e. cutting as a control, bud set and bud chip, toward seed quality and the early growth of cane plant in the field. This study was conducted in Tridarma research field, Faculty of Agriculture, Gadjah Mada University, Yogyakarta on September 2012 until March 2013, and transplanting of two month old seedling was done on November 2012. This study used factorial 6x3 in completly randomize (RAL) design, with two factor, which are six clones of sugarcane and three types of seedling materials that are cutting, bud set, and bud chip. The results showed that there were an interactions between both factors on germination rate, vigor index, leaf numbers, internode numbers, tillers numbers, leaf area, root volume, root fresh weight, root dry weight, shoot fresh weight, and shoot dry weight. The early growth of the cane plants was dependent on the clone. According to shoot fresh weight, cutting was suitable for PS 881 and Bululawang clones. Bud sett for PS 864 clone, whereas bud chip for PSJT 941 and Kidang Kencana. Three seedling materials could be fitted to Bululawang and VMC 86-550.